Learning Environment Design and Social Emotional Development in Early Childhood: Desain Lingkungan Belajar dan Perkembangan Sosial Emosional pada Masa Kanak-kanak - Lili Rismalah Defi; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Early childhood education emphasizes social emotional development as a foundation for children’s adaptation, relationships, and self-regulation. Specific Background The learning environment, including physical settings, social interactions, and psychological climate, is considered a central context shaping daily experiences in kindergarten classrooms. Knowledge Gap However, detailed descriptions of how these environmental components function collectively to support social emotional growth in specific early childhood institutions remain limited. Aims This study aimed to describe the role of the learning environment and to identify supporting and inhibiting factors related to social emotional development among children aged 4–5 years at TK Islam Al Wafa. Results Using a descriptive qualitative approach through observation, interviews, and documentation, the findings show that organized classrooms, play corners, consistent routines, teacher guidance, and peer interaction facilitate empathy, cooperation, discipline, and emotional expression, while family constraints and limited responsiveness hinder progress. Novelty The study provides an integrated description of physical, social, and emotional elements within one institutional case. Implications These results offer practical guidance for teachers and early childhood managers in structuring supportive learning environments to foster balanced social emotional competencies. Keywords: Learning Environment, Social Emotional Development, Early Childhood Education, Classroom Climate, Qualitative Study Key Findings Highlights: Structured spaces encourage cooperation and sharing behaviors Daily routines cultivate self-regulation and discipline Teacher guidance and peer play build empathy and communication